Gender-based Dayah: The Role of Female Ulama in Trauma Recovery Strategies for Sexual Violence Victims in Aceh - Fathayatul Husna; Ainal Fitri (Sawwa: Jurnal Studi Gender, 2023)
This article delves into the escalating cases of sexual violence in Aceh and the imperative need for trauma recovery efforts. Umi Hanisah, an Acehnese female ulama and founder of Dayah Diniyah Darussalam, the sole gender justice-oriented Islamic boarding school in Aceh, is pivotal in addressing this issue. Employing a descriptive qualitative approach, this research explores Umi Hanisah’s endeavors to heal the trauma of child victims of sexual violence. Data collection includes in-depth interviews, observation of the Dayah environment, documentation, and literature studies. Findings reveal Umi Hanisah’s authoritative approach in accommodating and recovering victims through a religious lens. She contends that the Islamic religious approach can emancipate victims from the chains of trauma, supplemented by Aceh’s local wisdom values as a foundation for trauma recovery, empowering victims to reintegrate into their communities.